2011
DOI: 10.1523/jneurosci.4068-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

A Wide Diversity of Cortical GABAergic Interneurons Derives from the Embryonic Preoptic Area

Abstract: GABA-containing (GABAergic) interneurons comprise a very heterogeneous group of cells that are crucial for cortical function. Different classes of interneurons specialize in targeting specific subcellular domains of excitatory pyramidal cells or other interneurons, which provides cortical circuits with an enormous capability for information processing. As in other regions of the CNS, cortical interneuron diversity is thought to emerge from the genetic specification of different groups of progenitor cells withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
156
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(169 citation statements)
references
References 49 publications
11
156
2
Order By: Relevance
“…MGE, Dg, and PoA are all involved in the production of neocortical inhibitory interneurons ( Fig. 10 A), and it has been shown that the progenitor zones of each of these domains produce distinct interneuronal subtypes [Gelman et al, 2011;Ma et al, 2013;Puelles et al, 2016]. Neocortical inhibitory interneurons generated in the subpallium enter the pallium through two different routes, i.e., a deep path within the intermediate zone between the pallial matrix and the cortical plate, and a superficial trajectory within the marginal zone ( Fig.…”
Section: Although Most Developing Neurons Migrate Radially and Settlementioning
confidence: 99%
“…MGE, Dg, and PoA are all involved in the production of neocortical inhibitory interneurons ( Fig. 10 A), and it has been shown that the progenitor zones of each of these domains produce distinct interneuronal subtypes [Gelman et al, 2011;Ma et al, 2013;Puelles et al, 2016]. Neocortical inhibitory interneurons generated in the subpallium enter the pallium through two different routes, i.e., a deep path within the intermediate zone between the pallial matrix and the cortical plate, and a superficial trajectory within the marginal zone ( Fig.…”
Section: Although Most Developing Neurons Migrate Radially and Settlementioning
confidence: 99%
“…Unlike glutamatergic projection neurons, which derive from proliferative regions in the dorsal telencephalon (Angevine and Sidman 1961;Rakic 1972;Tan et al 1998), cortical interneurons are largely born within distinct progenitor zones of the subcortical basal ganglia and populate the forebrain through long-distance tangential (nonradial) migration during late embryonic and early postnatal development Tamamaki et al 1997). In rodents and primates (Anderson et al 2001;Nery et al 2002;Hansen et al 2013;Ma et al 2013), including humans, the majority of cortical interneurons derive from two transitory regions of the ventral lateral ventricle in the embryonic telencephalon, the medial and caudal ganglionic eminences (MGEs and CGEs, respectively), with a smaller contribution from the preoptic area (POA) (Gelman et al 2011).…”
Section: Origins Of Cortical Interneuronsmentioning
confidence: 99%
“…The migration of the POa-derived cells is poorly understood, although recently this population has been revealed to be the source of GABAergic In utero electroporation, E11.5 to E13.5 neurons in the neocortex and the amygdala (8)(9)(10). The present findings show that the POa-derived cells that were migrating to the neocortex and the amygdala initially shared the migratory stream and then took separate paths controlled by the dynamic expression of COUP-TFII and Nrp2.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies using Nkx5.1-Cre and Dbx1-Cre mice show the preoptic area (POa) as a new source of cortical GABAergic neurons containing an Lhx6-expressing population (8,9). Other investigators report that the POa supplies GABAergic neurons to the medial nucleus of amygdala, in a study using Dbx1-Cre knock-in mice (10).…”
mentioning
confidence: 99%